Screening uncalibrated priority pollutants by improved AHP-CRITIC method at development land - Xinni Wei; Xiuli Dang; Peng Liu; Ge Gao; Hang Zhu; Jiayue Shi; Qiyuan Zhang; Roland Bol; Peng Zhang; Iseult Lynch; Long Zhao (Environment International, 2025)
Unlisted uncalibrated pollutants in the industrial land of northeast China are continuously accumulating due to insufficient regulatory control, posing a serious threat to the ecological environment and human health. To address this challenge and begin to quantify the currently unlisted uncalibrated pollutants present in the industrial land in northeast China, 170 candidate pollutants were screened based on the literature research method. The Analytical Hierarchy Process (AHP) and the Criteria Importance Through Intercrieria Correlation (CRITIC) were utilized equally to screen for priority control of unlisted uncalibrated pollutants. For the categorical indicators, local modifications were implemented on the toxicity, persistence, and migratory indicators, fully considering the industrial distribution, environmental traits, and pollutant sources in northeast China. The grading standards of these indicators were refined in accordance with the relevant criteria and the availability of monitoring data collected from databases and predicted data by models. 11 types of uncalibrated priority pollutants were screened out using the comprehensive evaluation method and conducting cluster analysis based on total pollutant scores. The order of pollutants identified as candidates for prioritized control measures was as follows: perfluorooctanoic acid (PFOA)＞acrolein＞perfluorooctane sulfonate (PFOS)＞styrene＞perfluorobutanoic acid (PFBA)＞anthracene (Ant)＞methyl isocyanate (MIC)＞2,4-dimethylphenol＞hexachlorobutadiene (HCBD)＞2,6-dimethylphenol＞perfluorononanoic acid (PFNA). In particular, PFOA has the highest concern with 382 points. It poses long-term and serious potential hazards to the ecological environment and human health of industrial sites in northeast China. Thus, controlling such key pollutants is crucial for northeast China’s environmental protection, and the current work supports the prioritization of chemicals for management or remediation.